2014
DOI: 10.1111/rec.12076
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Low‐Cost Planting Techniques for Improving Water Availability toOlea europaeaSeedlings in Degraded Drylands

Abstract: Reforestation projects in semiarid lands often yield poor results. Water scarcity, poor soil fertility, and structure strongly limit the survival and growth of planted seedlings in these areas. At two experimental semiarid sites, we evaluated a variety of low-cost planting techniques in order to increase water availability to plants. Treatments included various combinations of traditional planting holes; waterharvesting microcatchments; stone or plastic mulches; small waterproof sheets to increase water harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 38 publications
3
26
1
3
Order By: Relevance
“…As demonstrated in other studies, watering can increase survival and improve root growth during the establishment period, particularly when water supplements are applied during the summer season in semiarid environment [21,47,48,51,57]. However, our findings suggest that differences in water-acquisition strategies of root systems of South American Mediterranean tree species determine different capacity to survive under situations of severe drought.…”
Section: Discussioncontrasting
confidence: 54%
“…As demonstrated in other studies, watering can increase survival and improve root growth during the establishment period, particularly when water supplements are applied during the summer season in semiarid environment [21,47,48,51,57]. However, our findings suggest that differences in water-acquisition strategies of root systems of South American Mediterranean tree species determine different capacity to survive under situations of severe drought.…”
Section: Discussioncontrasting
confidence: 54%
“…In particular, woodchip had no positive effects on the recovery of vegetation although it reduced run‐off and soil erosion. These results agree with other studies about mulching in semiarid climate, where no clear effects were observed in plants and the results depended on mulch type and its thickness (Dodson & Peterson, ; Santana et al, ; Valdecantos et al, ). However, mulches effect on soils seems to be of more interest in areas with high soil erosion susceptibility (Jacobs, ; Jordán, Zavala, & Gil, ).…”
Section: Discussionsupporting
confidence: 92%
“…The evidence for a positive relationship between seedling growth and the size of the upslope microcatchment area should be considered when designing conservation and restoration actions in semiarid lands. On the one hand, treatments that exploit and enhance source-sink dynamics on dryland slopes can improve the re-introduction of native shrubs into areas under strong water-stress conditions (Valdecantos et al, 2014). On the other hand, with the aim of recovering previous landscape processes and minimizing resource leaks (Ludwig et al, 1999), the spatial pattern of the introduced seedlings should pursue a functional patchiness and source:sink area ratio, that maximizes both vegetation cover and the amount of water input that can be captured by the vegetation.…”
Section: Discussionmentioning
confidence: 99%